Marine gastropod at the intertidal zone of Rutong Village, Ambon Island as an indicator of water quality - Haumahu, Sara; Uneputty, Prulley A.; Natan, Juliana (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2024)
Studies on marine gastropod diversity as an indicator of water quality in Maluku province are rare. The research objectives are to study marine gastropod species composition and analyze its ecological density, abundance and frequency of occurrence, as well as to analyze an ecological index at the intertidal zone of Rutong village, Ambon Island, Maluku. 53 species of marine gastropods found in the intertidal zone, belonging to 41 genera, 22 families and 6 order. Muricidae, Neritidae and Tegulidae were marine gastropod families with higher ecological density and abundance. Some dominant species known as key species in this region were Nerita spatula, Rochia nilotica, Tenguella granulate, Nassarius pullus, Clypeomorus battilariaeformis, Monetaria annulus, Monodonta calanifera and Conus miles. Generally, the species of marine gastropods in this study area have limited distribution. Shannon-Wiener diversity index (H`) of marine gastropods is in a medium to high category, which varies between 1.56 to 3.46. Meanwhile, Pielou’s evenness index (J`) is in the stable category, in which the value was from 0.61 to 0.95 Whereas, Simpson's dominance index varied from 0.05-0.30, which is in the low category. The coastal water of Rutong village can be categorized as moderately polluted waters to unpolluted waters.